Tuning of NK-Specific HLA-C Expression by Alternative mRNA Splicing - Goodson-Gregg, Frederick J.; Rothbard, Brian; Zhang, Amy; Wright, Paul W.; Li, Hongchuan; Walker-Sperling, Victoria E.; Carrington, Mary; Anderson, Stephen K. (Frontiers in Immunology, 2020)
A complex system regulating HLA-C expression in NK cells, driven by an NK-specific promoter that produces alternatively spliced variants of the 5´-UTR has been recently identified. Exon content of the NK-specific 5´-UTR varies strikingly across HLA-C alleles, with some exons being allele-specific. In order to investigate the possibility that allelic variation in the 5´-UTR modulates HLA-C expression levels, cDNAs containing several distinct classes of 5´-UTR were compared. Subtle changes in 5´-UTR content had a significant effect on the expression of HLA-C*03, HLA-C*04, and HLA-C*12 cDNA clones, suggesting that alternative splicing can fine-tune the level of protein expression. The HLA-C*06 allele was found to be highly expressed in relation to the other alleles studied. However, its increased expression was primarily associated with differences in the peptide-binding groove. Although the impact of allele-specific alternative splicing of NK-Pro transcripts on protein levels can be modest when compared with the effect of changes in peptide-loading, alternative splicing may represent an additional regulatory mechanism to fine-tune HLA-C levels within NK cells in distinct tissue environments or at different stages of maturation in order to achieve optimal levels of missing-self recognition.